Pemikiran Pendidikan Mohammad Sjafe'i: Kaitannya dengan Kurikulum Merdeka Belajar - Hardi, Etmi; Gistituati, Nurhizrah; Bentri, Alwen (Journal of Moral and Civic Education, 2023)
This study examines the relationship between Mohammad Sjafe'i educational ideas and the self-learning curriculum in schools. Education is an effort to help students develop normatively better in the intellectual, moral, and psychological dimensions. Mohammad Sjafe'i's educational thinking contains character values with the active-creative method he has developed, which can encourage students to learn actively and independently. This research is using qualitative descriptive methods. The data were obtained through interviews, observations, and document studies. The results of this study prove that Sjafe'i's thinking is in line with the current education curriculum in Indonesia, which implements an independent learning curriculum. An independent learning curriculum is a lesson plan that provides opportunities for students to study in a calm, comfortable, relaxed, enjoyable, and pressure-free manner to show their natural talents. This self-study curriculum focuses on student freedom and creative thinking.